The saints of Swallow Hill - Everhart, Donna (Kensington Publishing Corp., 2022)
In Georgia's Swallow Hill turpentine camp in 1932, Rae Lynn Cobb, disguised as a man, hides out from those who would wrongly accuse her for murdering her husband and struggles to survive harsh, brutal conditions with the help of two individuals with their own tragic pasts.